The myth of the shrinking state globalization and the state in India - Nayar, Baldev Raj 1931- (Oxford Univ. Press, 2009)
"This book investigates the impact of globalization and liberalization on the state in India. It challenges the argument that an inevitable concomitant of globalization is the erosion, and possible dismantlement, of the economic and welfare roles of the state. Bringing to bear the weight of abundant empirical evidence on the question, the book documents the continued expansion of the state's economic and welfare roles." "This book will interest researchers and students of politics, economics, and international relations. It will also be useful to administrators, policymakers, and all those interested in the contents and discontents of globalization."--BOOK JACKET.